The prognostic value of the myeloid-mediated immunosuppression marker Arginase-1 in classic Hodgkin lymphoma - Romano, Alessandra (Oncotarget, 2016)
PURPOSE: Neutrophilia is hallmark of classic Hodgkin Lymphoma (cHL), but its precise characterization remains elusive. We aimed at investigating the immunosuppressive role of high-density neutrophils in HL. EXPERIMENTAL DESIGN: First, N-HL function was evaluated in vitro, showing increased arginase (Arg-1) expression and activity compared to healthy subjects. Second, we measured serum level of Arg-1 (s-Arg-1) by ELISA in two independent, training (N = 40) and validation (N = 78) sets. RESULTS: s-Arg-1 was higher in patients with advanced stage (p = 0.045), B-symptoms (p = 0.0048) and a positive FDG-PET scan after two cycles of chemotherapy (PET-2, p = 0.012). Baseline levels of s-Arg-1 > 200 ng/mL resulted in 92% sensitivity and 56% specificity to predict a positive PET-2. Patients showing s-Arg-1 levels > 200 ng/mL had a shorter progression free survival (PFS). In multivariate analysis, PET-2 and s-Arg-1 at diagnosis were the only statistically significant prognostic variables related to PFS (respectively p = 0.0004 and p = 0.012). Moving from PET-2 status and s-Arg-1 level we constructed a prognostic score to predict long-term treatment outcome: low s-Arg-1 and negative PET-2 scan (score 0, N = 63), with a 3-Y PFS of 89.5%; either positive PET-2 or high s-Arg-1 (score 1, N = 46) with 3-Y PFS of 67.6%, and both positive markers (score 2, N = 9) with a 3-Y PFS of 37% (p = 0.0004). CONCLUSIONS: We conclude that N-HL are immunosuppressive through increased Arg-1 expression, a novel potential biomarker for HL prognosis.